2000
DOI: 10.1002/1096-8628(20000828)93:5<366::aid-ajmg5>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Association between presenilin-1 polymorphism and maternal meiosis II errors in Down syndrome

Abstract: Several lines of evidence suggest a shared genetic susceptibility to Down syndrome (DS) and Alzheimer disease (AD). Rare forms of autosomal-dominant AD are caused by mutations in the APP and presenilin genes (PS-1 and PS-2). The presenilin proteins have been localized to the nuclear membrane, kinetochores, and centrosomes, suggesting a function in chromosome segregation. A genetic association between a polymorphism in intron 8 of the PS-1 gene and AD has been described in some series, and an increased risk of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 71 publications
2
15
0
1
Order By: Relevance
“…For example, as mentioned in the introduction, significant numbers of trisomy 21 and other aneuploid cells have been found in both sporadic and familial AD patients, including individuals carrying a mutation in PS-1 or PS-2 [9,26,31,49,50]. Similarly, two polymorphisms in PS-1, one in the coding sequence and one in the promoter have been found to be associated with both an increased risk of AD and an increased incidence of Down syndrome offspring due to chromosome missegregation during meiosis [24,29]. The finding of endogenous presenilin proteins in structures related to mitosis-centrosomes, kinetochores, and the nuclear envelope -also suggests that PS-1 and 2 play a role in the cell cycle and chromosome segregation [13,18,22].…”
Section: Discussionmentioning
confidence: 95%
“…For example, as mentioned in the introduction, significant numbers of trisomy 21 and other aneuploid cells have been found in both sporadic and familial AD patients, including individuals carrying a mutation in PS-1 or PS-2 [9,26,31,49,50]. Similarly, two polymorphisms in PS-1, one in the coding sequence and one in the promoter have been found to be associated with both an increased risk of AD and an increased incidence of Down syndrome offspring due to chromosome missegregation during meiosis [24,29]. The finding of endogenous presenilin proteins in structures related to mitosis-centrosomes, kinetochores, and the nuclear envelope -also suggests that PS-1 and 2 play a role in the cell cycle and chromosome segregation [13,18,22].…”
Section: Discussionmentioning
confidence: 95%
“…Indeed, a polymorphism in the PS-1 gene is associated with both an increased risk of developing AD and of having a Down syndrome child (Wragg et al , 1996; Higuchi et al , 1996; Petersen et al , 2000; Lucarelli et al , 2004). Furthermore, immunocytochemical and FRET results have shown that endogenous PS-1 and APP and some of their interacting proteins reside in cell structures involved in mitosis, such as the nuclear membrane, centrosomes, or kinetochores (Zimmermann et al , 1988; Li et al , 1997; Honda et al , 2000; Johnsingh et al , 2000; Kimura et al , 2001; Tezapsidis et al , 2003; Zitnik et al , 2006; Nizzari et al , 2007) and become hyperphosphorylated during mitosis (Pope et al , 1994; Suzuki et al , 1994; Preuss et al , 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Among the known predisposing factors, advanced maternal age is by far the strongest [1] and, independently of maternal age, genetic mapping shows that certain types of cross‐over at maternal meiosis I confer a substantial susceptibility to non‐disjunction [2]. Parental DNA studies have reported an altered distribution of polymorphisms in the genes for apolipoprotein E, presenilin‐1 and those involved in folate metabolism, but the effects are not great and the results inconsistent between studies [3–6]. Numerous hypotheses have been suggested to explain the underlying mechanism, in particular the maternal factors, in the aetiology of DS, but it remains an enigma [7].…”
mentioning
confidence: 99%